Influence of Fit-checking Material and Cleaning Protocols on the Bond Strength of Lithium Disilicate Glass-ceramics - Marchioro, R. R.; Pini, Nip; Kelmer, V. F.; Freitas, Kms; Santos, P. H. [UNESP]; Pacheco, R. R.; Sundfeld, D. (Operative Dentistry, 2022)
OBJECTIVES: To evaluate the bond strength of a resin luting agent to a lithium disilicate glass-ceramic after the use of different fit-checking materials and cleaning protocols. METHODS AND MATERIALS: Two hundred and forty-two (242) ceramic specimens were etched with 5% hydrofluoric acid for 20 seconds and distributed into 22 groups (n=10), in total. Four (4) groups were created based on fit-checking material and that had no following cleaning protocol: no fit-checking material used (control group); articulating paper; articulating spray; and fit-checker liquid. For each fit-checking material (3), 6 cleaning protocols were tested creating an additional 18 groups (n=10): air/water spray; 70% alcohol (ethanol); acetone; 35% phosphoric acid; 5% hydrofluoric acid; and a commercially available cleaning paste (Ivoclean, Ivoclar Vivadent). Silane and bonding resin were applied to all ceramic surfaces. Resin luting agent cylinders (1 mm in diameter) were created using silicone matrices, light-cured, and specimens were stored in deionized water at 37°C for 24 hours. Microshear bond strength test (μSBS) was performed on a universal testing machine (DL 500, EMIC) at a crosshead speed of 1 mm/min until failure. Results were statistically analyzed using ANOVA and Tukey's test (α=0.05). RESULTS: Articulating paper and fit-checker liquid, when not properly removed, negatively affected the bond strength (p<0.05). None of the tested cleaning protocols were effective for articulating paper (p<0.05). There was no significant difference in bond strength after the cleaning protocols between articulating spray and fit-checker liquid when compared to the control group (no contamination) (p>0.05). CONCLUSION: The cleaning protocols tested can effectively restore the bond strength of resin luting agents to lithium disilicate ceramics that were exposed to articulating spray or fit-checker liquid. The use of articulating paper is not recommended for fit-checking indirect lithium disilicate restorations.